1990
DOI: 10.1111/j.1365-2796.1990.tb00194.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute renal failure and non‐Hodgkins lymphoma in a patient with minimal change glomerulonephritis

Abstract: Two rare features of minimal change glomerulonephritis occurring together in an adult patient are described. A 70-year-old man presented with acute renal failure and the nephrotic syndrome. Investigation revealed minimal change glomerulonephritis and non-Hodgkins lymphoma. Anti-lymphoma treatment reversed both the renal failure and the nephrotic syndrome. Minimal change glomerulonephritis, as a cause of acute renal failure and as a manifestation of malignancy, is briefly reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Functional abnormalities of B cells and T cells, and increased or decreased levels of immunoglobulins, have also been reported [14,16]. Nephrotic syndrome occurs frequently in association with various malignant processes, including some carcinomas, and hematological malignancies (malignant lymphoma [9][10][11], and CLL [13][14][15]). Nephrotic syndrome occurs frequently in association with various malignant processes, including some carcinomas, and hematological malignancies (malignant lymphoma [9][10][11], and CLL [13][14][15]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional abnormalities of B cells and T cells, and increased or decreased levels of immunoglobulins, have also been reported [14,16]. Nephrotic syndrome occurs frequently in association with various malignant processes, including some carcinomas, and hematological malignancies (malignant lymphoma [9][10][11], and CLL [13][14][15]). Nephrotic syndrome occurs frequently in association with various malignant processes, including some carcinomas, and hematological malignancies (malignant lymphoma [9][10][11], and CLL [13][14][15]).…”
Section: Discussionmentioning
confidence: 99%
“…Eagan and Lewis [20] reviewed 52 cases of Hodgkin's disease with nephrotic syndrome, and found minimal change nephrotic glomerulonephritis in 50% of them. In non-Hodgkin's lymphoma, minimal change glomerulonephritis and mesangial proliferative glomerulonephritis are less frequently observed than in Hodgkin's disease [10,22]. It has been suggested that impairment of T-cell mediated immunity induces minimal change nephrotic glomerulonephritis in Hodgkin's disease [9,21].…”
Section: Discussionmentioning
confidence: 99%
“…Renal function is usually not altered in minimal-change glomerulonephritis associated with Hodgkin's disease [&lo]. In contrast, the more severe types of NHL-associated glomerulonephritis frequently result in full-blown nephrotic syndrome [7,8,48,50,53,56,, impaired renal function [7][8][9]11,46], or renal failure [41,47,49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas renal failure in idiopathic nephrotic syndrome rarely responds to treatment, renal function in lymphomaassociated glomerulonephritis generally improves after initiation of chemotherapy and may even return to normal [8,11,41,43,46,49,50,60]. However, renal function in NHL-associated glomerulonephritis may be normal at time of diagnosis [8] and deteriorate subsequent to chemotherapy 1 1 1 3 1 1.…”
Section: Discussionmentioning
confidence: 99%
“…Glomerular lesions have been de scribed during the course of Hodgkin's disease [5], The most common renal lesion is minimal-change disease with ne phrotic syndrome (41 cases described in the literature). Nephrotic syndrome usually occurs early in the course of the disease and may even constitute a presenting symptom [6,7], Cure of the disease usually results in remission of proteinuria [8], Nephrotic syndrome may announce a re lapse of the hematological disorders [9], Crescentic glomer ulonephritis associated with anti-G BM antibodies has been reported in 6 cases of Hodgkin's disease [5] (whereas circu lating anti-G BM antibodies were always present). In our observation, extended survey eliminated the possibility of recurrence of Hodgkin's disease, and there were no anti-GBM antibodies found.…”
Section: Discussionmentioning
confidence: 99%